Solidarity - Aramayo, Roberto R. (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: The aim here is to address the ascription of solidarity to a complex conceptual constellation in which could be found such terms as altruism, compassion, empathy, fraternity, or even philantropy, trying to avoid at the same time what is implied by other words like benevolence, charity, pity, mercy or piety. Being a successor of everything symbolizing fraternity, solidarity itself cannot be enough in demand in a context where values related to the homo oeconomicus come first. That would be more the reason to revisit solidarity from the vantage point posed by enlightened values. Thus, going over Kantian concepts like autonomy and independence, joined those by Rousseau’s reflections on inequality, both seem to claim for an interdependence not tainted by aporophobia or promoting the lack of solidarity, but instead by the indispensable social justice.
Keywords: Solidarity; fraternity; autonomy; interdependence; inequality; aporophobia; social justice; Kant; Rousseau; Doménech; Muguerza